The Influence of Students’ Level Ability of Reading Comprehension on The Students’ Translation Ability - Fita Faridah; Syafi'ul Anam (Jurnal PTK dan Pendidikan, 2022)
This study focused on the influence of reading comprehension ability on translation ability, and we classify reading based on score into three categories they are low, moderate, and high. The data analysis used the statistical formula of SPSS; the data tests were normality and homogeneity tests. Hypothesis testing in this study was carried out using a one-way analysis of variance (One Way ANova). The finding of this study was there was a significant effect on reading level into translation. Therefore, it could be concluded that Ho was rejected, meaning that there was a significant difference between the students’ reading level into translation ability. Implication research for helping teacher for reading comprehension this effect translation.